Analisis Kualitas Kinerja Keuangan Daerah Provinsi Maluku Tahun 2017-2021 - Abidin Tatroman; Kismon Monierdin; Kumba Digdowiseso (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The quality of the Maluku Province's financial performance is measured by the degree of decentralization ratio showing the low financial performance of the Maluku Province in 2017-2021 out of a total count of eleven city districts. If you calculate the total average value of the degree of decentralization ratio for 2017-2021 Maluku Province is 4.09%. This figure illustrates that the quality of Maluku Province's financial performance is very low in the 2017-2021 period. The financial independence ratio of Maluku Province is instructive with the average percentage of districts/cities below 25%, meaning that Maluku Province's dependence on central government assistance is quite large for financing regional development. The regional financial effectiveness ratio of Maluku Province is in the category of ineffective regional financial performance. Of the eleven regencies/cities of Maluku Province, only five regencies/cities are categorized as effectively balanced, but the 2017-2018 period is not complete for the 2017-2021 period. The accumulative total analysis shows that Maluku Province is classified as an ineffective regional financial province. Keywords: Quality of financial performance; Maluku Province.